The effects of MOTILIPERM on cisplatin induced testicular toxicity in Sprague–Dawley rats. Issue 1 (December 2015) - Soni, Kiran; Zhang, Li; You, Jae; Lee, Sung; Kim, Chul; Cui, Wan; Chae, Han; Kim, Hye; Park, Jong
Abstract Background Cisplatin causes male infertility but the exact mechanism have not been clarified, yet. MOTILIPERM has been implicated in alleviation of infertility in Sprague–Dawley rats caused by cisplatin. We evaluated recovery effect of MOTILIPERM on cisplatin (CIS)-induced testicular toxicity in Sprague–Dawley rats. Methods Five groups were included. The groups are control (CTR), CTR + MOTILIPERM 200 mg/kg/day per oral, CIS 10 mg/kg i.v., CIS 10 mg/kg + MOTILIPERM 100 mg/kg/day, CIS 10 mg/kg + MOTILIPERM 200 mg/kg/day. CIS 10 mg/kg i.v. single dose was given before 100 mg/kg, or 200 mg/kg MOTILIPERM per oral daily for 28 days. Body and genital organs weight, epididymis sperm count, sperm motility, sperm apoptosis, testosterone level, MDA of testis tissue, spermatogenic cell density, and Johnsen's score were evaluated. Steroidogenic acute regulatory (StAR) protein, and Glucose-regulated protein-78 (GRP-78), phosphorylated Inositol-Requiring Transmembrane Kinase/Endoribonuclease 1 (IRE1) and phosphorylated c-jun-N-terminal kinase (p-JNK) were quantitated by western blot to show its signaling pathway. Results The body weight was decreased significantly in CIS 10 mg/kg, CIS 10 mg/kg + MOTILIPERM 100 mg/kg/day, CIS 10 mg/kg + MOTILIPERM 200 mg/kg/day compared with CTR (p < 0.001) however, it was increased in CIS 10 mg/kg + MOTILIPERM 100 mg/kg/day, CIS 10 mg/kg + MOTILIPERM 200 mg/kg/day compared with CIS 10 mg/kg. The decreased weight of epididymis and prostate were increased significantly in CIS 10 mg/kg + MOTILIPERM 100 mg/kg/day compared with CIS 10 mg/kg. Sperm count, sperm motility, sperm apoptosis, MDA of testis tissue, spermatogenic cell density, Johnsen's score, and total testosterone were also significantly improved by MOTILIPERM treatment. The levels of decreased StAR protein was significantly improved by MOTILIPERM administration, increased GRP-78 protein p-IRE1and p-JNK was also significantly decreased with MOTILIPREM treatment. Conclusion The MOTILIPERM could be an effective medicine to reduce the toxic effect caused ER stress by CIS in the testis.